AKUNTABILITAS PENGELOLAAN DANA DESA DI DESA ARENAN KECAMATAN KALIGONDANG KABUPATEN PURBALINGGA TAHUN 2020-2021 - Saraswati, Saraswati; Amanda, Arista; Sutikno, Chamid (Badan Perencanaan Pembangunan Penelitian dan Pengembangan Daerah Kabupaten Cilacap, 2023)
Accountability for Village Fund Allocation Management in Arenan Village, Kaligondang District, Purbalingga Regency for 2020-2021. Aims to analyze the Accountability of Village Fund Allocation Management in Arenan Village, Kaligondang District, Purbalingga Regency in the 2020 and 2021 fiscal years. Using the theory of the accountability dimension from Ellwood in Mardiasmo 2018 and the 2020-2021 Purbalingga Regent Regulation concerning ADD. The research method used is a qualitative research method. Collecting data using interviews, observation and documentation. Furthermore, the data will be analyzed using Creswell data analysis techniques. The results of the study show that the management of Village Fund Allocations in Arenan Village, Kaligondang District, Purbalingga Regency. Looking at it from an accountability perspective, it is in accordance with existing regulations in managing ADD from planning to accountability. There is supervision from several related parties and trying to be transparent regarding financial information. However, in 2020 there is a lack of accountability, namely lack of transparency in showing the 2020 village meeting documents and delays in reporting in 2020.